364 km ultra-long Raman fiber laser based on high-order pumping and ultra-low-loss fiber. (June 2023) - Dong, Shisheng; Han, Bing; Wu, Han; Deng, Kangye; Liu, Yang; Rao, Yunjiang
Highlights: The effect of pumping scheme and key fiber parameters to further extend the ultimate length of Raman fiber laser is explored. The method of combination of higher-order pumping and ultra-low-loss fiber to increase the cavity length of Raman fiber laser is proposed and verified. A 364 km-long ultra-long Raman fiber laser is demonstrated. Abstract: Raman fiber laser (RFL) based on distributed Raman gain along optical fiber is an ideal platform for realizing ultra-long-cavity laser, which is of great interest in fundamental laser science and multidisciplinary fundamental studies such as complex systems exhibiting turbulence-like characteristics. RFL based on standard single-mode fiber sets the record of the longest laser cavity reaching 270 km with a clearly resolvable mode structure. Here, we explore the effect of pumping scheme and key fiber parameters to further extend the ultimate length of RFL. We theoretically analyze and experimentally demonstrate that by adopting higher-order pumping and ultra-low-loss fiber (ULLF) with low transmission loss and low Rayleigh backscattering coefficient, the laser cavity length of RFL with resolvable mode structure can be significantly increased. As a result, a 364 km-long bi-directional pumped 6th-order ultra-long Raman fiber laser (URFL) based on ULLF is demonstrated with resolvable longitudinal mode, an extension of 35 % over the prior 270 km record. This work paves a way to lengthen cavity length of URFL and provides a new platform for fundamental laser physics study and the ultra-long fiber laser applications in communication and sensing.